A study on customer's perception on the atmosphere of Body Shop, The Mall / Fauziah Din - Din, Fauziah (1998)
Store atmosphere is the overall aesthetic and emotional effect created by the store's physical features; it is the total sensory experience created by the store. To create a store atmosphere conducive to buying, Body Shop, The Mall has tried to establish its own image in consumer's mind that supposed to promote a buying spirit. The store atmosphere's being studied in this research is about the shop's atmosphere and how customers perceive this atmosphere elements. The reason is to identify the strengths and weaknesses to enable the company to improve its image and sales. The elements of the shop which are being studied are on its exterior; the marquee, window display, size of the shop, while the interior consists of color coordination, lighting, temperature, service , merchandising and layout of the shop. Besides the store atmosphere, the value being concerned in this study is about Body Shop's business itself This business offers customers the chance to choose an entire human system. Today, each shop globally, continues to trade on the same principles that shaped its beginnings that are, to use naturally-based, close to source ingredients, offer a range of sizes on rninimum packaging so that customers pay only for the product, rather than elaborate, unnecessary packaging.